Determinants of adoption of sustainable agricultural practices by small-scale coffee farmers in amazonas, Peru - Guevara-Fernandez, Francisco; Oliva-Cruz, Manuel (Asian Journal of Agriculture and Rural Development, 2025)
This study seeks to examine the factors affecting the adoption of SAPs and their intensity of use at the smallholder household level in four coffee producer districts of Luya, Amazonas, Peru, based on cross-sectional survey data obtained from 145 sampled households, six coffee farmer interviews, and three expert interviews. Despite the benefits of Sustainable Agricultural Practices (SAPs), their use rate among small-scale farmers is still low in developing countries like Peru. The results showed that coffee farmers adopted different SAPs according to several factors that determine their adoption; those factors can be farm(er)-related, sustainable practices’ attributes, and communication and extension. Moreover, drawing on the logistic regression technique (logit), the marginal effects of the critical factors that significantly determine the adoption of SAPs were obtained. The logit results evidenced that coffee farmers’ decision to adopt SAPs was influenced by the number of people of working age living in the household for cover crop and composting, farmland slope for living or dead barriers, coffee yield and educational attainment for fertilization, and number of assets and facilitating conditions for wastewater treatment. The main problems are the lack of workers for integrated pest management, the focus on making money on farms for agroforestry, and people’s fears about taking risks with cover crops. The findings provide actionable insights for policymakers and development practitioners aiming to foster sustainable farming practices in similar contexts.